THE EFFECT OF CHICKEN MANURE ON THE GROWTH AND YIELD OF PURPLE LONG BEAN ON ALLUVIAL - Marudur, Reni; Bandem, Putu Dupa; Zulfita, Dwi (Jurnal Sains Mahasiswa Pertanian, 2020)
This study aimed to find the best dosage of chicken manure on the growth and yield of the purple long bean (Vigna sinensis L.) on the alluvial soil. The research was conducted at the research field of Agricultural Faculty Tanjungpura University Pontianak from April 19th - June 23th 2019. The Completely Randomized Design (CRD) was used in the experiment with 5 levels of chicken manure dosage and 5 replications respectively. The levels of chicken manure dosage were 400, 800, 1.200, 1.600 dan 2.000 grams/polybag consecutively. The observed variables were root volume, chlorophyll content of leaf, plant dry weight, the fruit number per plant, and fruit weight per plant. The results showed that the best dosage of chicken manure for growth and yield of purple long bean (Vigna sinensis L.) was 1.200 grams/polybags equivalent to 15% chicken manure of the soil weight.Keywords: Alluvial, chicken manure, purple long bean.